Wind Turbine Effects on Power System Voltage Fluctuations - Erduman, A.; Kilickiran, H. C.; Kekezoglu, B.; Durusu, A.; Tanrioven, M. (IEEE, 2013)
Every passing day wind energy becomes more indispensable part of power systems. So this increasing require the analysis of wind turbine impact on the grid. In this study, possible effect of wind turbine which is connected to Turkish distribution grid are analyzed. Distribution grid system is modeled with NEPLAN power system analysis simulator program. Finally, results are presented.
Keywords: wind turbines; grid connection; voltage fluctation; Energy & Fuels; Engineering